0131 Planes, Trains And Automobiles: Traffic Noise And Its Impact On Sleep Depth Measured By Odds Ratio Product. (12th April 2019) - Smith, Michael G; Younes, Magdy; Aeschbach, Daniel; Müller, Uwe; Basner, Mathias
Abstract: Introduction: Traffic noise events can lead to cortical and autonomic activation, disrupt sleep and impair physical and mental restoration. The odds ratio product (ORP) is a validated continuous measure of sleep depth and quality, based on automatic analysis of EEG data in 3s epochs. More so than traditional manual scoring of sleep in 30s epochs or the binary scoring of arousals, ORP allows tracking temporal changes of sleep in response to external stimuli. Here we examine event-related changes in ORP in response to nocturnal noise events. Methods: Seventy two healthy participants (mean age 40 years, range 18-71; 40 women) slept for 11 nights in the laboratory, during which sleep was measured with polysomnography. In 8 nights they were exposed to 40, 80 or 120 road, rail and/or aircraft noise events at maximum sound pressure levels between 45-65 dBA. Event-related maximum change of ORP in a 90s window relative to pre-event baseline was analyzed with linear mixed models. Results: Average whole night ORP increased with age (β=0.008; p<0.001), indicating decreasing sleep depth, but was not significantly affected by the average nighttime noise level or number of noise events. For events where participants were asleep at noise onset (n=29, 663), ORP increased monotonically with sound pressure level (F(4, 27964)=88.4; p<0.001) for all traffic modes. There was a main effect of traffic mode (F(2, 25809)=58.6; p<0.001) on ORP, with a higher response to road (p<0.001) and rail (p<0.001) noise than to aircraft. The magnitude of ORP increase depended on sleep stage at noise onset, decreasing in the order of S2, SWS, REM (F(3, 20955)=133.9; p<0.001), but recovery time to pre-event baseline ORP was in the reverse order. ORP change decreased as a function of age (β=-0.002; p=0.004). There were no significant effects of noise duration, sex or sleep spindle density on event-related ORP change. Conclusion: Traffic noise led to increased ORP in an exposure-dependent manner, reflecting decreased sleep depth and quality. The clinical relevance of event-related elevations of ORP is currently unknown, and warrants further investigation. Support (If Any): None